Still in the Danger Zone - Jonathan Nitzan; Shimshon Bichler (The Bichler and Nitzan Archives, 2020)
In December 2017, we posted a RWERB entry, titled `Profit warning: there will be blood'. We warned that, although the Weapondollar-Petrodollar Coalition might no longer be in the Middle East driver's seat, the oil and armament companies, the region's oil-exporting autocracies and various non-state groups were all keen on seeing their oil incomes rise from record lows. And we ob-served that, in this context, `the prospects of a new energy conflict, whether premeditated or co-incidental, seem extremely high'. [. . .] We can only hope that the current round of Middle East hostilities won't be proportional to the size of its current danger zone.
Keywords: P16; D74; Q4; 330; differential accumulation; Middle East Energy Conflicts